Investigating the Cybersecurity Implications of Open Banking and Application Programming Interfaces (APIs) in the Financial Sector - Hossain, Mohammad Amir; Raza, Md. Adil; Rahman, Jami Yaseer (Jurnal Ekonomi dan Bisnis Digital, 2025)
Open banking and the use of APIs within the financial industry are improving how financial services are delivered by stimulating innovation, enhancing competition, and providing customer-oriented solutions. But that evolution has also brought its own heavy cybersecurity challenges. In this article we focus on the cybersecurity risks of open banking and APIs, including issues such as data breaches, and risks from third-party entities. Based on case studies, vulnerability assessments, and interviews with experts, the study highlights key threats and analyzes existing mitigation measures such as secure API development, authentication protocols, and regulatory compliance frameworks. Results highlight the need for strict cybersecurity measures built upon a Zero Trust Architecture, including the use of an API gateway and regular penetration testing to secure sensitive financial data, safeguarding an open banking landscape. The results of this research will assist financial institutions, developers, and regulators in securing next-generation open banking platforms without hindering innovation and risk management.